Simulation of L-Topology matching networks for MMIC applications - Dizon, Jefferson C.
The project aimed to design and characterize L-topology networks for Microwave Monolithic Integrated Circuit (MMIC) applications. We have built on and expanded the previous projects of Conti and Macoy (Interdigital Capacitor Design for MMIC Applications) and Bueta and Lat (Characterization of Spiral Inductor Topologies for GaAs MMIC Applications) and have integrated their capacitor and inductor designs to develop passive matching networks. CST Microwave Studio, a 3-dimensional electromagnetics simulator, was used for simulation and characterization of the networks. In the design of these networks, we have focused in the matching networks' properties such as the S11 parameters and the total quality factor. As for the capacitors and inductors, the trends of the results (due to parameter variations) from the previous MMIC works were used in determining base designs. Included in the characterization of the base designs are the variation of substrate height, feedline width, feedline length, metal thickness and topologies.